Discovery and structure–activity relationships of a novel oxazolidinone class of bacterial type II topoisomerase inhibitors. (1st June 2022) - Lyons, Amanda; Kirkham, James; Blades, Kevin; Orr, David; Dauncey, Elizabeth; Smith, Oliver; Dick, Emma; Walker, Rolf; Matthews, Teresa; Bunt, Adam; Finlayson, Jonathan; Morrison, Ian; et al.
Graphical abstract: Abstract: There is an increasingly urgent and unmet medical need for novel antibiotic drugs that tackle infections caused by multidrug-resistant (MDR) pathogens. Novel bacterial type II topoisomerase inhibitors (NBTIs) are of high interest due to limited cross-resistance with fluoroquinolones, however analogues with Gram-negative activity often suffer from hERG channel inhibition. A novel series of bicyclic-oxazolidinone inhibitors of bacterial type II topoisomerase were identified which display potent broad-spectrum anti-bacterial activity, including against MDR strains, along with an encouraging in vitro safety profile. In vivo proof of concept was achieved in a A. baumannii mouse thigh infection model.